2015
DOI: 10.1080/10426914.2015.1019102
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Machining Process Combining Micro-EDM and Laser Beam Machining of Nickel–Titanium-Based Shape Memory Alloy

Abstract: Micro-EDM is a slow process as compared to laser machining, on the contrary laser machining lacks good surface quality. To overcome the drawbacks of both these processes, this paper suggests a hybrid machining process which combines laser and micro-EDM processes for drilling micro-holes in advanced engineering materials such as Nickel-Titanium (Ni-Ti) based shape memory alloy. To achieve the objective of the suggested hybrid process, pilot holes are drilled with laser machine and rimmed out by micro-EDM drilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 23 publications
1
34
0
1
Order By: Relevance
“…The NiTi alloy is in martensitic phase at low temperatures and in the austenitic phase at high temperatures [4]. A review of the literature showed that different manufacturing processes are used for the machining of NiTi alloy such as laser processing method [5][6][7][8][9][10][11][12][13][14][15][16], electrical discharge machining (EDM) [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], electrochemical polishing [32] and abrasive water jet processing method (AWJM) [33,34] for shaping NiTi alloy and also conventional machining methods (Turning [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], milling…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NiTi alloy is in martensitic phase at low temperatures and in the austenitic phase at high temperatures [4]. A review of the literature showed that different manufacturing processes are used for the machining of NiTi alloy such as laser processing method [5][6][7][8][9][10][11][12][13][14][15][16], electrical discharge machining (EDM) [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], electrochemical polishing [32] and abrasive water jet processing method (AWJM) [33,34] for shaping NiTi alloy and also conventional machining methods (Turning [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], milling…”
Section: Introductionmentioning
confidence: 99%
“…The surface roughness change diagrams of NiTi shape memory alloy with tungsten carbide tools at two different nose radii (0.4 mm and 0.8mm) and three different cutting speeds(20,35, and 50 m/min).…”
mentioning
confidence: 99%
“…In case of ultrasonic-assisted EDM (UAEDM), combining of EDM with ultrasonic vibrations is found to be one of the most effective shared hybrid machining processes with increased metal removal rate during machining of electrically conductive very hard materials [157]. Hybrid machining process which combines laser and micro-EDM processes for drilling microholes in complex engineering materials such as nickel-titanium (Ni-Ti)-based shape memory alloy (SMA) is an example of recent use of hybrid machining process technique [158].…”
Section: Hybrid Machining Process Using Edmmentioning
confidence: 99%
“…Image of rough machined workpiece with (a) conventional tool and (b) tool prepared by rapid tooling [44] Murray et al and Naveen Beri et al (2014) published works on the surface treatment and enhancing the surface wear and corrosion properties using the PM processed electrodes [67].…”
Section: Figure 10mentioning
confidence: 99%